Ecological support of reserves as a factor in the efficiency of using the circulating assets of a construction enterprise. - Izmaylovа, K. (Ways to Improve Construction Efficiency, 2018)
The main directions of the currently required environmental maintenance of building material stocks at the construction site have been considered. The impact of measures on the environmental maintenance of stocks on their requirement, i.e. on the reallocation of the enterprise's means for one of the most significant components of the working capital, has been analized.